Newsworthiness of reform: prison news stories in an era of change - Cecil, Dawn K. (Journal of crime and justice, 2019)
Media representations of prison have been cited as a source of information for those who do not have personal experience with these institutions. While found in various facets of the media, the news media can offer immediate information about prison-related issues. Traditionally, news coverage of prison has featured negative stories about escaped inmates, riots, and abusive guards, and their messages have served to justify get tough policies. Combined these types of news stories have contributed to penal populism. In recent years, efforts aimed at fixing the damage done by the imprisonment binge have become prevalent. What is not known is how the news media are covering these reform efforts. This study examines prison news articles published in The New York Times during 2015 to determine if and how prison reform efforts are being covered. While traditional prison news stories are still being published, prison reform was newsworthy. Readers were exposed to bipartisan arguments supporting prison reform, while simultaneously receiving messages that these changes would not apply to violent offenders.